Urgensi Kolaborasi Orang Tua Dan Guru Pendidikan Agama Kristen Dalam Mewujudkan Pendidikan Spiritual Efektif Bagi Anak - Rezeki Putra Gulo; Agus Mawarni Harefa (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2023)
Actualizing effective spiritual education for children is a very, very important thing. To achieve this, collaboration between parents and PAK teachers is needed. Children are the next generation. For this reason, every child must receive proper and correct spiritual education. This is so that children's lives can be educated in the truth of God's word and can live according to His commands written in the Bible. However, without the collaboration of parents and PAK teachers, it is certain that the child's spiritual education will not be realized satisfactorily. For this reason, what is needed is for the two educators to collaborate well in realizing effective spiritual education for children. This article uses a qualitative method with a literature research approach. The efforts made aim to contribute ideas to the weakening collaboration of parents and PAK teachers in meeting the spiritual needs of children. The final conclusion in this study is that the collaboration of parents and PAK teachers is needed in realizing effective spiritual education for children.